Trajectory tracking control for four-mecanum-wheeled robots considering mass eccentricity: A fuzzy adaptive and dynamic surface control approach - MINH DONG NGUYEN; Hiep, Do Quang; Nam, Dao Phuong; Tien, Ngo Manh (Journal of Computer Science and Cybernetics, 2025)
This paper presents a novel approach combining Fuzzy adaptive control with dynamic surface control to enhance trajectory tracking of four mecanum wheeled mobile robots considering mass eccentricity. Mass eccentricity, which refers to the displacement of the robot’s center of mass, poses significant challenges for precise control and stability. The proposed combined control strategy addresses these challenges by leveraging the adaptive capabilities of fuzzy logic and the robustness of dynamic surface control. Simulation results demonstrate that this approach significantly improves trajectory tracking accuracy and system stability